Triple-Threat Pregnancy: Navigating PPCM, Preeclampsia, and Thalassemia Major – A Holistic Reproductive Risk Assessment Post-Cesarean Delivery - Arya Ady Nugroho; Yudianto Budi Saroyo; Dwiana Ocviyanti (MEDICINUS, 2026)
Background: Pregnancies complicated by multiple severe maternal conditions such as peripartum cardiomyopathy (PPCM), preeclampsia, and β-thalassemia major, pose significant risks to both mother and fetus. This case explores the challenges of managing a high-risk pregnancy, involving these conditions and highlights the importance of a multidisciplinary approach in high-risk pregnancy management.Case presentation: A 33-year-old pregnant woman with β-thalassemia major presented at 32+4 weeks of gestation with acute dyspnea, severe preeclampsia, and signs of PPCM. She was carrying dichorionic diamniotic twins and required emergency cesarean section after stabilization. Echocardiography revealed severe left ventricular systolic dysfunction with an ejection fraction of 35%. The patient underwent immediate postoperative management and received a trans-cesarean intrauterine device (IUD) insertion for long-term contraception. Both neonates were admitted to the neonatal intensive care unit (NICU) for prematurity care.Conclusion: This case underscores the critical need for a holistic, multidisciplinary approach in managing complex highrisk pregnancies, focusing on immediate maternal stabilization, neonatal care, and long-term reproductive planning.